The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1016/0928-8244(94)00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring virulence-attenuated isolates of Listeria monocytogenes capable of inducing long term protection against infection by virulent strains of homologous and heterologous serotypes

Abstract: Experimental infections of mice with strains of Listeria spp. isolated from contaminated food sources allowed discrimination of strains into those either exhibiting high, attenuated or low virulence. Compared to the highly virulent L. monocytogenes strain EGD, an attenuated strain such as L99 persisted for shorter times (5 versus 10 days) in the infected host. Using a tissue culture cell model of infection, we found that, although strain L99 was capable of accumulating actin like its virulent counterpart follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
(27 reference statements)
2
22
0
1
Order By: Relevance
“…In contrast, Wiedmann et al (1997) reported a mean plaque size for lineage III isolates (n=5) that was significantly larger than the 10403S control (126?2±6?8 %). In that study, however, one small plaque-forming isolate (L99, plaque size 53?5±7?9 %) was excluded from analysis based on its previously reported virulence-attenuated phenotype (Chakraborty et al, 1994). When isolate L99 is included, however, the mean lineage III plaque size is 114±30 %, which is not significantly different from the mean plaque size for the lineage III isolates characterized here.…”
Section: Cell Culture Characterization Of Lineage III Isolatesmentioning
confidence: 80%
“…In contrast, Wiedmann et al (1997) reported a mean plaque size for lineage III isolates (n=5) that was significantly larger than the 10403S control (126?2±6?8 %). In that study, however, one small plaque-forming isolate (L99, plaque size 53?5±7?9 %) was excluded from analysis based on its previously reported virulence-attenuated phenotype (Chakraborty et al, 1994). When isolate L99 is included, however, the mean lineage III plaque size is 114±30 %, which is not significantly different from the mean plaque size for the lineage III isolates characterized here.…”
Section: Cell Culture Characterization Of Lineage III Isolatesmentioning
confidence: 80%
“…One of the major reasons we chose the SNaPshot multiplex kit is the ease through which the assay developed in this study can be modified to accommodate the detection of additional genetic markers by simply designing new extension primers and combining them into another multiplex reaction mixture. While previous studies described the presence of virulenceattenuating mutations in other key L. monocytogenes virulenceassociated genes (i.e., actA, hly, and inlB), only a single isolate or a few isolates were reported to carry these mutations (3,20,24,32). Mutations leading to the truncation of virulence factors other than InlA were not included in the SNP genotyping assay developed in this work because these mutations do not appear to have been accumulated at the population level and have not been shown to be responsible for attenuated virulence through the characterization of isogenic mutants in appropriate animal infection models.…”
Section: Vol 74 2008 Snp Detection Of Virulence-attenuated L Monocmentioning
confidence: 91%
“…However, these strains showed hybridization with lmaD and lmaC probes, suggesting that they probably harbor a deletion of the lmaBA genes. Heterogeneity in the expression of virulence traits in strains belonging to serogroup 4 has repeatedly been reported in the literature (4,38). We also analyzed L. innocua 6a, a serotype in which several strains have previously been reported to harbor the lmaA gene (15).…”
Section: Discussionmentioning
confidence: 99%